Assessment of Physico-Chemical and Bacteriological Quality of Jar Water Marketed In Kathmandu Metropolitan City - Panthi, Grishma; Shakya, Bhushan (Amrit Research Journal, 2024)
Samples of water supplied in 20 litre jars under ten different brand names were collected randomly from several places of Kathmandu metropolitan city. Analyses of various physico-chemical parameters of water conducted. Water from each jar is analysed for physical parameters (pH, electrical conductivity (EC) and total dissolved solids (TDS)) and chemical parameters (total hardness (TH), calcium, magnesium, total alkalinity (TH), chloride, nitrate and iron) and for bacterial contamination. These analyses assess jar water suitability in Kathmandu district, revealing some company must improve processors and enhance hygiene and comply with NDWQS and WHO standards.